Political parties and political recruitment (study on the recruitment of the Golkar party coalition and PPP in nominating pairs of candidates for regent and deputy regent candidates in Demak regency in 2015) - Cendhy Vicky Vigana (Central Research Institute for Agriculture (CeRIA), 2021)
This thesis focuses on the analysis of attention on the recruitment of political candidates for the Regent and Deputy Regent candidates, which were promoted by the coalition of the Golongan Karya (Golkar) party and the United Development Party (PPP) in the 2015 Pilkada of Demak Regency. The purpose of this study was to analyze the recruitment mechanism for the 2015 regional head candidates for Demak Regency, which were promoted by the Golkar and PPP parties. This study is interesting and important to do considering the lack of studies on the recruitment of political candidates in political constellations in the struggle for political office, at the local level, especially in the 2015 Simultaneous Regional Elections. The purpose of this research is to describe two things: first, what makes the Golkar Party and PPP nominated the candidate pair for regent and deputy regent of Demak Regency who were not from the party's own cadres; second, what are the factors that made the Golkar Party form a coalition with PPP in Demak Regency in the 2015 local elections. The findings show that despite all the obstacles, obstacles and challenges faced by each party (both Golkar and PPP). So that it can be said that the Golkar and PPP parties are not seriously committed to carrying their cadres as candidates to be carried out in the 2015 Demak Regency election contestation.